Evaluation the effect of different types of adhesives on the bond strength of zirconia full crown restorations on different teeth: In vitro study - Amaal Khalleefah Altabeeb; Marwa Mawulud Elhtab (African Journal of Advanced Pure and Applied Sciences, 2025)
Introduction: Zirconia full crown are a popular choice for dental restoration due to their strength and natural appearance. However, the clinical effectiveness of these restorations is significantly influenced by the type of adhesive used. Adhesives play a crucial role in creating a solid and long-lasting link between the restoration’s surface and the tooth structure, increasing resistance to chewing pressures and oral environmental changes. Aim: To determine the effect of different types of adhesives on the bond strength and stability of zirconia restorations on anterior and posterior teeth. Methodology: A study involving 12 samples of human teeth was conducted to compare the retention strength of three different types of (adhesives Dual-cure resin cement, Glass-reinforced resin cement, One-step multipurpose adhesive). Results: showed that the dual-cure resin adhesive was the best option, with average retention strengths of 450 N for anterior teeth and 620 N for posterior teeth. This adhesive can withstand increased chewing pressures and has superior bonding properties. However, the glass fiber-reinforced resin adhesive showed modest capacity for retention with average stresses of 390 N for anterior teeth and 540 N for posterior teeth. The one-step multipurpose adhesive performed poorly with average retention forces of 320 N for anterior teeth and 480 N for posterior teeth. Conclusion: Dual-cure resin adhesives should be given priority by dentists, especially for posterior teeth that experience strong occlusal pressures.